The Innovator's DNA : Mastering the Five Skills of Disruptive Innovators - Dyer, Jeff [et al.] (Boston Harvard Business Review Press, 2011)
Some people are just natural innovators, right? With no apparent effort, they discover ideas for new products, services, and entire businesses. This title identifies five capabilities demonstrated by the innovators: Associating; Questioning; Observing; Experimenting; and, Networking.
Include Index and Notes
Keywords: Technological innovations -- Creative ability in business -- Entrepreneurship